KECENDERUNGAN PILIHAN MASYARAKAT SUKU PETALANGAN MEMILIH PENGOBATAN TRADISIONALDI DESA BETUNG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Yulia Ananda Putri; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The tendency of the Petalangan community to choose the treatment greatly influences the health of the Petalangan community in Betung Village, Pangkalan Kuras Subdistrict, Pelalawan District. Health is very important because it affect human productivity. The strong belief of the people of Petalangan towards traditional medicine makes people have other reasons for modern medicine. Therefore the researchers tried to analyze what the tendency of the Petalangan community to traditional medicine in the village of Betung is. In this study, researches used the theory of health belief models. This study condists of 6 respondents consisting of traditional / religious leaders, village midwives, and Betung villagers. The results of this study indicate that people’s choice of traditional and modern medicine is very good, society accepts that modern medicine is very good, society accepts that modern medicine is an irrevocable progress and has also helped the community in terms of achieving healing but they still cannot leave traditional medicine from their ancestors because it is considered valuable and has been proven to cure people from illness during this time and become the main choice in treatment.Keywords : Health, Betung Village, Petalangan Tribe, Treatment